Meningkatkan Minat Baca Anak-anak Melalui Cerita Rakyat Lokal: Program Dongeng dan Kreativitas Untuk Membuka Dunia Imajinasi - Novia, Lisa; Firdausi, Isha Ananda; Darmawan Putri, Salwa Rulla; Fitri, Silhana; Hamzah, Yusuf; Srihayani (Sekolah Tinggi Ilmu Manajemen Sukma Medan, 2024)
The low interest in reading and the declining attention toward local folklore among early childhood children pose a serious challenge to cultural resilience and national literacy quality. This Community Service (PKM) activity aims to increase reading interest and stimulate the imagination of children at PAUD Glora Hati, Pondok Aren, through a storytelling and creativity program. The implementation method utilized an edutainment approach that combines storytelling techniques using hand puppet media with interactive letter-arrangement games. The stages of the activity included orientation, delivery of the